A Comparative Study of Phonological Variations Between Ku͂ɽux and Kuɳha - Xalso, Albin Rico; Arulmozi , S. (Nepalese Linguistics, 2025)
Ku͂ɽux and Kuɳha are North Dravidian indigenous languages spoken by the Oraon and Kisan communities, respectively, in the Chotanagpur plateau, primarily in Jharkhand, Bihar, Chhattisgarh, West Bengal, Odisha, Assam, and in areas outside India, including Nepal and Bangladesh. The origin myths of both communities reveal that both communities sprang from a common proto-language. Baxla (2015) states 75% of the vocabulary has a similarity index between the two languages. The present study highlights the phonological variations between the two languages. It provides a clear understanding of the phonological systems of both languages, in particular, and of Dravidian studies in general.